1994
DOI: 10.1039/c39940001101
|View full text |Cite
|
Sign up to set email alerts
|

Novel oxidative conversion of β,γ-unsaturated acids into butenolides: synthesis of heritonin and heritol

Abstract: A novel strategy of converting P,y-unsaturated esters to butenolides involving oxidative cyclisation with ceric ammonium nitrate at room temperature is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This strategy has been used by Chavan and co-workers for conversion of β , γ-unsaturated acids into butenolides mediated by CAN. They applied this protocol for the synthesis of biologically active molecules such as heritonin …”
Section: 2 Alkoxylation Reactionsmentioning
confidence: 99%
“…This strategy has been used by Chavan and co-workers for conversion of β , γ-unsaturated acids into butenolides mediated by CAN. They applied this protocol for the synthesis of biologically active molecules such as heritonin …”
Section: 2 Alkoxylation Reactionsmentioning
confidence: 99%
“…79 Later on, another group in the same institute reported that b,g-unsaturated esters can be converted into butenolides in high yield by oxidative cyclization with ceric ammonium nitrate (CAN) at room temperature. 80 The above-reported approaches to butenolides both started from a-tetralone, and differed only in how the butenolide ring was constructed. In 2004, Silveria reported a new strategy to (AE)-heritonin, which employed b-tetralone as the starting compound (Scheme 3).…”
Section: Heritiera Littoralismentioning
confidence: 99%
“…In continuation of our work in the synthesis of biologically active molecules viz. heritol 1, 2 heritonin 2, 3 heritianin 3, vallapin 4, 3 vallapianin 5 3 and related compounds we have reported 4,5 novel methodologies for the synthesis of butenolides from the corresponding b,g-unsaturated esters and acids.…”
mentioning
confidence: 96%